Hope in Cancer Patients: The Relational Domain as a Crucial Factor. Issue 4 (July 2015) - Proserpio, Tullio; Ferrari, Andrea; Vullo, Salvatore Lo; Massimino, Maura; Clerici, Carlo Alfredo; Veneroni, Laura; Bresciani, Carlo; Casali, Paolo G.; Ferrari, Mauro; Bossi, Paolo; Galmozzi, Gustavo; Pierantozzi, Andrea; et al.
Aims and background: Hope is crucial for patients with cancer. We explored the determinants of hope in patients with cancer using a questionnaire administered over the course of 1 day to an unselected sample of patients at an Italian cancer center. Methods: A team of oncologists, statisticians, and chaplains developed a questionnaire with medical, psychological, spiritual, and religious content. A cross-sectional study was conducted on 320 patients who answered the questionnaire. Results: In the group of participants, 92.8% had a religious belief. Women, patients with limited formal education, and believers were more hopeful. Patients placed trust in God, their partners and children, scientific research, and doctors. On univariate and multivariate analysis, hope was found sensitive to patients' sharing their experiences with others (including family and friends), their positive perception of the people around them, and their relationship with doctors and nurses. Conclusions: If validated in further studies, these results support the notion that a patient with cancer's sense of hope is sensitive to the quality of relationships with caregivers. This may be important to health care organization and resource allocation.